Spectrum of variants in the filaggrin gene in the Russian population and in patients with ichthyosis vulgaris - I.V. Zavarina; A.A. Kechin; O.V. Dolya; R.E. Mikheeva; N.A. Oskina; E.E. Baranova (Russian Journal of Clinical Dermatology and Venereology, 2026)
Background. The filaggrin protein, encoded by the FLG gene, is key to maintaining a healthy skin barrier and normal immune system function. Filaggrin loss-of-function mutations are the primary cause of ichthyosis vulgaris, a common dermatological disorder. At the same time, high variability in individual variant frequencies between the studied populations and a large number of repeats in the third exon significantly complicate gene analysis using standard PCR methods. Objective. To examine the spectrum of genetic variants in the FLG gene associated with ichthyosis vulgaris in a cohort of Russian patients using whole-exome sequencing and analysis of publicly available data on this gene’s polymorphism. Material and methods. Clinical examination and molecular genetic testing were performed on 77 patients diagnosed with ichthyosis vulgaris (ICD-10: Q80.0) at the Moscow Scientific and Practical Center of Dermatovenereology and Cosmetology (MSPCDC). Whole-exome sequencing (WES) was done to analyze the coding region of the FLG gene in DNA samples from peripheral blood leukocytes. To analyze the spectrum of genetic variants across the Russian Federation (RF), a database of population frequencies of the RF was used. Results and conclusion. Among 120 762 individuals whose FLG gene variant data were evaluated in the RF population frequency database, 292 different pathogenic and likely pathogenic variants were identified, of which only 78 were registered as pathogenic in the ClinVar database. All detected variants were mapped across the amino acid sequence of the protein with a relative enrichment in the region of filaggrin repeats. The overall carrier frequency of pathogenic variants was 8.0%, of which the 3 most common pathogenic variants (p.Ser761fs, p.Arg2447* and p.Arg501*) accounted for 5.6%. Furthermore, individual allele frequency ratios relative to the gnomAD database varied from 0.06× to 26×, which indicates significant differences in the spectrum of pathogenic variants compared to global statistics. Obtaining whole-exome data for patients with ichthyosis vulgaris allowed us not only to confirm the pathogenicity of the p.Ser761fs variant, identified in 32 of 77 patients, but also to reveal the previously undescribed p.Ser1515* variant. The large number of variants of uncertain significance (2475), most of which are missense substitutions, suggests the need for in vitro functional testing, segregation studies, and comparison of their frequencies among patients with the disease and in the general population from Russia. In addition, there are ongoing doubts in the scientific community regarding the pathogenicity of many nonsense and frameshift mutations. Accordingly, the obtained overall frequency of pathogenic variants may be revised in the future. Thus, in this study, the spectrum of pathogenic variants in the FLG gene was determined for the first time among patients with ichthyosis vulgaris and within a general population sample from Russia.